2015
DOI: 10.1016/j.ijpam.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Research training, productivity and challenges among trainees of pediatric residency programs across Saudi Arabia

Abstract: Background and objectives: Research provides skills for lifelong learning and promotes patient care. In Saudi Arabia, until recently, research training has not been integrated effectively in postgraduate medical education. The aim of this study was to investigate the factors involved in research training, productivity, challenges and attitude among trainees in paediatric residency programs across Saudi Arabia. Materials and methods: This is a cross-sectional, multicentre study using a questionnaire designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Several factors influence research training and productivity in medical sectors in Saudi Arabia. According to Alhaider et al, [10], a lack of research topics, research questions, research tools, and time are considered the main personal factors that affect the research productivity in paediatric residency programmes across Saudi Arabia.…”
Section: Personal Factors (Personal Use Of Ict)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors influence research training and productivity in medical sectors in Saudi Arabia. According to Alhaider et al, [10], a lack of research topics, research questions, research tools, and time are considered the main personal factors that affect the research productivity in paediatric residency programmes across Saudi Arabia.…”
Section: Personal Factors (Personal Use Of Ict)mentioning
confidence: 99%
“…[78]. CP4: I believe attending or presenting in scientific conference will improve my research productivity [10]. CP5: I believe publishing books or chapters will enhance my research productivity [26].…”
Section: Sample Of Questionnairementioning
confidence: 99%
“…The results of the program evaluation in the reaction level of the Kirkpatrick model showed that participants and other stakeholders were not generally satisfied with the program. Although most recent similar programs did not measure satisfaction as a primary outcome, participants often reported positive reactions to these research courses such as a rise in research interest, 19 valuable research experience, 2,20,21 and exposure to qualified learning program. 22 Findings from the evaluation of the "learning" level revealed that most participants did not reach a satisfactory level of knowledge and skills in research.…”
Section: Discussionmentioning
confidence: 99%
“…Similar programs reported an increase in the publication rate 2,20 ; some reported that despite participating in the training program, residents did not engage in research projects as expected. 21,29,30 We could not find a criterion to assess sufficient publication rates; most programs aim to enhance residents' scholarly activity, that is, increasing the number and rate of publication. Other studies have not reported a high-quality publication rate, nor have they used a quality assessment tool to evaluate proposals, theses, or papers.…”
Section: Discussionmentioning
confidence: 99%
“…As high as 86.7% never published an article, and 78.3% did not present oral nor poster presentations before. 3 On a regional level, 73.9% of 142 Bahraini residents had an opportunity to participate in research, with considerably lesser trainees reported presenting oral or poster presentations (around 23.2% and 31%, respectively). 4…”
Section: Introductionmentioning
confidence: 99%